Influência da interenxertia e dos sistemas de condução nas propriedades funcionais do pêssego. - Manica-Berto, Roberta (2008)
The peach has in its composition bioactives compounds that can help in the retardation of aging and prevention of certain diseases. With the necessity to consider the existing interaction it among practices management and the functional attributes for, thus, getting significant advances in the referring studies the capacity antioxidant in the fruits, the objective of this work was to study the influence of the length interstock and diferent training systems in the functional properties on peaches, by an evaluation of its physicochemical and chemical characteristics.The experiments were carried out at Palma Agriculture Center (CAP/UFPel) during the 2007/08 growing season. In first experiment, was used peach tree orchard Jubileu‟ intergrafting with filters of Granada‟ with 0, 5, 10, 15 and 20 cm of length. In the laboratory, the effect of fruit parts (peel and flesh) for chemical variable was considered. In second experiment peach orchards Jubileu‟ and Eldorado‟ was used under diferent training systems on Capdeboscq rootstock. The treatments had been: cultivate - Jubileu and Eldorado, training systems - vase, central leader and y fruit parts (peel and flesh). In both experiments physicochemicals variables evaluated: average weight fruits, classification, peel color (L*, a*, b* and h°), flesh firmness, SST, ATT, pH and SST/ATT. Chemicals variables evaluated: antioxidant activity, total carotenoids, L-ascorbic acid and total phenols. In general, the interstock, independently of the length of filters, did not affect the physicochemical and chemicals characteristics. However, the training systems had influenced, directly, physicochemical characteristics in peaches Jubileu‟ and Eldorado‟. Specifically, peaches Eldorado‟ trained as an Y concentrated, in the peel, greater increasing total carotenoids.